Determination of the loads on the steering module of the push-the-bit rotary steerable system in the context of its reliability; Acta Montanistica Slovaca; Vol. 25, iss. 3 - Zhironkin V. S. Vitaly Sergeevich; Epikhin A. V. Anton Vladimirovich; Novoseltsev D. S. Denis; Cehlar M. Michal (2020, 2020)
Title screen